Confucius's Doctrine as a Part of Political Language of Modern China - Ionova Anastasiya (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2014)
As the title implies, the article describes Confucius study as a part of political language. It gives the detailed analysis of different public acts and documents, various media publications and speeches of Chinese politicians which demonstrate the influence of Confucius ideas on the political language of modern China and shows the degree of their reflection in the political lexis. First of all, Confucius had thought that the speech should be simple, clear and short. It should come from the bottom of your soul. Confucius believed that social disorder often stemmed from failure to perceive, understand, and deal with reality. Fundamentally, social disorder can stem from the failure to call things by their proper names, and his solution to this was rectification of names. If names are not correct, language is not in accordance with the truth of things, and it leads to unsuccessful business. The author shows how these speech requirements influence the political language today. The article goes on to say that not all Confucius ideas are used in the political language. Sometimes politicians can change the actual meaning and employ them for their own profits. Among other ideas modern politicians emphasize the idea of rectification of names, the idea of the importance of continuity, the idea of significant meaning of connections between generations, humaneness, laws which should be based on justice, and the idea of honest officials. The article proves that the influence of Confucius is manifested not only in the specific political decisions, but also in political language.